Association of ABO Blood group phenotypes with FEV1/FVC values among students of Aziz Fatima Medical and Dental College - Zahid, Hira; Rehman, Anam; Zareen, Saima; Rasheed, Sana; Jawed, Shireen; Altaf, Benash (Journal of Rawalpindi Medical College, 2024)
Objective: To find the frequency of obstructive and restrictive lung disease in various blood groups in young students of Aziz Fatimah Medical and dental college. Methods: This cross-sectional analytical study was conducted at Aziz Fatima Medical and Dental College, Faisalabad from 1st January to 31st March 2022. It included 80 participants of first-year MBBS comprising both genders between 18 to 22 years. Ethical approval was taken from the institutional ethical committee of the institute. After fulfilling inclusion and exclusion criteria blood grouping was done by conventional slide method and Spirometry was performed to access lung function parameters to determine obstructive and restrictive lung diseases. Data was analyzed by using SPSS version 26. Results: The study population included 36 males (45%) and 44 females (55%). Mean±SD age of participants was 20 ± 1.07 years. The most frequent blood group was B followed by O, A and AB. Restrictive lung disease ( FEV1/FVC ratio ≥ 0.8) was found in 19(23.8%) participants while obstructive lung disease ( FEV1/FVC ratio <0.8) was found in 46(57.5%) participants. Obstructive lung diseases were more frequently found in subjects with blood group AB while restrictive lung diseases were more commonly noticed in subjects with blood group O. Mean±SD of FEV1/FVC% of subjects with obstructive and restrictive lung diseases were 45.15± 19.04 and 81.79±8.25 respectively. Conclusion: Blood group AB is more prone to have Obstructive lung disease with decreased FEV1/FVC ratio. Restrictive lung disease was more commonly seen in blood group O.